(untitled) (Journal of Pathology of Nepal, 2021)
Background: Cystic lesions of the scalp with a clinical diagnosis of an epidermoid cyst are encountered in clinical practice. However, these lesions had a different diagnostic interpretation on histopathology examination. Therefore our study focused on the lesions clinically resembling the presentation of epidermoid cyst in the scalp region. Materials and Methods: Forty-one cases of scalp lesions with a clinical diagnosis of epidermoid cyst over 2 years were reviewed. Details of the patients such as clinical diagnosis, age, gender, duration, gross findings, and histopathology diagnosis were obtained from the medical and histopathology records. Results: Epidermoid cysts diagnosed both clinically and on histopathology examination accounted for 29.26% whereas the clinical mimickers constituted 70.73%. The mean age of the patient was 35-years with an equal sex ratio. The commonest location was the parietal region (41.37%). Benign and malignant lesions consisted of 97.56% and 2.4% respectively. A trichilemmal cyst was the most common clinical mimicker diagnosed. Conclusions: Clinicians should be aware of wide differential diagnosis of epidermoid cyst in the scalp region as the management and outcome vary with each lesion. Histopathology examination proved to be a diagnostic tool in differentiating these lesions.